TINDAKAN KEPOLISIAN DALAM MENGUNGKAP TINDAK KEJAHATAN NARKOTIKA DI KOTA SAMARINDA - Hanun Cahyarsi (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRAK Crime is an act or action carried out by humans where the act is prohibited by criminal law. One of the crimes that often occurs in Indonesia is Narcotics. In general, Narcotics problems can be divided into three interrelated parts, namely the existence of illegal narcotics production, narcotics illicit trade, and narcotics abuse. The problem in this research is how is the law enforcement of narcotics criminal acts committed by the police, and what are the inhibiting factors in the law enforcement of narcotics crimes committed by the police.The study was conducted using a normative juridical approach and empirical jurisdiction. The data used are primary data and secondary while processing obtained by means of identification, editing, classification and systematic.The results of the study are described as follows: Law enforcement of narcotics criminal acts carried out by the Police is carried out by using revitative efforts, namely using legal remedies, where narcotics criminals must be prosecuted under Law No. 35 of 2009 concerning Narcotics. Police who carry out narcotics crimes are tried in a public peradila environment where the disciplinary witness will be carried out in a code of ethics session. Examination of polri discipline will be handled by the Head of the Department of Propam sub-sector. The prosecution of the defendant member of the Indonesian National Police was carried out by the Public Prosecutor. The development of prisoners of the National Police members was carried out in the prison. Whereas preventive measures are to provide guidance to the police by means of socialization. Factor Ankum law enforcers have not been maximal in giving sanctions to police officers who commit violations. Factors for facilities or facilities Related to problems with inadequate facilities and infrastructure and limited budget support. Community factors As well as the lack of public concern to report to the authorities, it is difficult for law enforcers to eradicate narcotics crimes. The background and personal characteristics of the Police members make it smarter. Keywords: Law Enforcement, Narcotics Crime, Police